Analisis Kesesuaian Implementasi Pembangunan Permukiman Inklusif di Kampung Blunyahrejo, Kelurahan Karangwaru, Kota Yogyakarta - Ningrum, Anatasya Devi Retno; Wahyuhana, Ratika Tulus (P4W IPB, 2023)
Rapid development of settlements and high population density may cause the availability of residential infrastructure inadequate and not in accordance with the technical standards of basic services. Sustainable Development (SDGs) include the realization of safe, resilient, inclusive and sustainable urban settlements. The Settlement Environmental Management Plan (RPLP) which is planned through the KOTAKU (Kota Tanpa Kumuh) program in Karangwaru Village, Yogyakarta, a plan intended to develop facilities and infrastructure with an inclusive approach. Despite so, the existence of settlement facilities in the village has not been adequate. This study aims to examine the suitability of implementation the Settlement Environmental Management Plan in Karangwaru Village in the development of inclusive settlements. The research method used is a qualitative approach with qualitative descriptive analysis methods. Results of the study indicate an increase in accessibility and housing facilities that are inclusive and friendly for persons with disabilities. The construction of a road network that is friendly to diffables, indicated the condition of settlements equipped with guiding blocks, markers, guides, safety lanes, marks a change towards inclusive settlements in Karangwaru Village. According to the results of interviews and observations, the provision of inclusive settlement facilities not optimal. There are four components that have been built, namely pedestrian paths, guideways, ramps and stairs. The implementation of inclusive settlement development in Karangwaru Village is not yet fully in accordance with the Settlement Environmental Management Plan and Ministerial Regulation of Public Works No.14/PRT/M/2017 about No.14/PRT/M/2017 concerning Building Requirements.